Novel Experiencer‐Object Verbs and Clitic Doubling. (9th May 2019) - Alexiadou, Artemis; Anagnostopoulou, Elena
Abstract: This article discusses novel experiencer‐object verbs (NEOs) and proposes to align their syntax as well as the syntax of nonagentive experiencer‐object verbs to the syntax of verbs undergoing the causative alternation under similar restrictions. We provide support for the view that (i) volitional agents do not occupy the same structural position as nonvolitional causers; (ii) VoiceP creates a phase, that is, a domain of compositional interpretation, and coercion into a psychological reading takes place in the absence of this layer; (iii) clitic doubling can be sensitive to animacy in a structure that lacks Voice and in which the clitic is the reflex of movement; and (iv) the accusative case morphology of experiencers both in eventive experiencer‐object constructions and our NEO constructions is straightforwardly explained as the result of dependent‐case assignment.